2017
DOI: 10.1055/s-0036-1590954
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Mediated C–N Bond Cleavage in 1-Sulfonylpyrrolidines: An Efficient Route towards Dibenzoxanthenes, Diarylmethanes, and Resorcinarenes

Abstract: The rare example of pyrrolidine C–N bond cleavage in 1-sulfonylpyrrolidines in acidic media in the presence of phenols is reported. The reaction proceeds under mild conditions and provides a convenient route to otherwise hardly accessible and previously unknown dibenzoxanthenes, diarylbutanes, and resorcinarenes having a sulfonylamide moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…The proposed mechanism of reaction is similar to the previously described mechanism of formation of polyphenols from 1‐(3,3‐diethoxypropyl)‐3,3‐di(aryl,alkyl)ureas (Scheme ) . The key step of the reaction is the elimination of the ethanol molecule from acetal 2 , which leads to the formation of the carbocation A .…”
Section: Resultsmentioning
confidence: 99%
“…The proposed mechanism of reaction is similar to the previously described mechanism of formation of polyphenols from 1‐(3,3‐diethoxypropyl)‐3,3‐di(aryl,alkyl)ureas (Scheme ) . The key step of the reaction is the elimination of the ethanol molecule from acetal 2 , which leads to the formation of the carbocation A .…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, we showed that reactions of nitrogencontaining acetals can also be used to prepare dibenzoxanthenes. [23][24][25] Thus, 2-naphthol and 2,7naphthalenediol were used in the reaction with acetals 2a,b in the presence of an excess of trifluoroacetic acid (Scheme 2). As a result, dibenzoxanthenes 4a-d were obtained in good yields (Table 1, entries 3-6).…”
Section: Scheme 1 Synthesis Of Acetals 2abmentioning
confidence: 99%
“…The proposed reaction mechanism is similar to that previously described for formation of polyphenols from N-(4,4-diethoxybutyl)sulfonylamides (Scheme 3). 24 The key step of the reaction is the elimination of methanol from acetal 2, which affords oxonium ion A. The next stage is the interaction of this species with phenolic nucleophile.…”
Section: Scheme 1 Synthesis Of Acetals 2abmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this, it is not surprising that much effort has been devoted to the development of novel approaches to these compounds. [4][5][6] At the same time, -aminophosphonic acids, as analogues of natural amino acids, play an important role in the investigation of biologically active molecules. [7][8][9] Among them, pyrrolidine derivatives possessing a phosphoryl moiety are of special interest due to their unique biological properties.…”
Section: Introductionmentioning
confidence: 99%